Bone repair induced by different bone graft substitutes in critical-sized defects in rat calvaria - Aroni, Mauricio Andrés Tinajero; Costa Neto, Paulo Firmino Da; Oliveira, Guilherme José Pimentel Lopes De; Marcantonio, Rosemary Adriana Chiérici; Marcantonio Junior, Elcio (Universidade Estadual Paulista Júlio de Mesquita Filho, 2019)
AbstractIntroduction The use of bone substitutes in grafting procedures as an alternative of the use of autogenous bone graft has been indicated, however, the direct comparison between these biomaterials has been little explored.Objective To evaluate the effect of different osteoconductive bone substitutes on the bone repair in critical-sized defects (CSDs) in rat calvaria.Material and method One CSD with an 8 mm diameter was made in each of the 40 rats used in this study. The animals were randomly allocated into 5 groups (n=8), according to the type of bone substitute used to fill the CSD: COA (Coagulum); AUT (autogenous bone); DBB (deproteinized bovine bone graft); HA/TCP (biphasic ceramic composed of hydroxyapatite and β-phosphate tricalcium); and TCP (β-phosphate tricalcium). A microtomographic analysis was performed to evaluate the remaining defect linear length (DLL) of the CSD and the volume of the mineralized tissues (MT) within the CSD at 3, 7, 15 and 30 days after the surgical procedure. In addition, a histometric analysis was performed to evaluate the composition of the repaired bone tissue (% Bone and % Biomaterial) at the 30-day period.Result It was shown that the COA had the lowest DLL and MT within the CSD. In addition, the COA presented the highest % of bone in CSD. The DBB had a higher MT and a higher % of bone substitute particles in the CSD than the AUT and TCP groups. The DBB and AUT groups presented higher % of bone in the CSD than the TCP group.Conclusion The use of the DBB promoted a better pattern of bone volume gain and formation compared to TCP and HA / TCP but was biologically inferior to the AUT.

ResumoIntrodução A utilização de substitutos ósseos em procedimentos de enxertia de forma alternativa ao uso do osso autógeno tem sido indicada, entretanto a comparação direta entre esses biomateriais tem sido pouco explorada.Objetivo Avaliar o efeito de diferentes biomateriais osteocondutores sobre o reparo de defeitos críticos em calvárias (DCC) de ratos.Material e método Foram utilizados 40 ratos que foram submetidos a confecção de um DCC com 8 mm de diâmetro. Os animais foram aleatoriamente divididos em 5 grupos com 8 animais, de acordo com o tipo de biomaterial utilizado para preencher os DCC: Grupo COA (coágulo); Grupo AUT (osso autógeno); Grupo OBD (osso bovino desproteinizado); Grupo HA/ TCP (cerâmica bifásica composta de hidroxiapatita e β fosfato tricálcio); Grupo TCP (β fosfato tricálcio). Foram executadas análise microtomográfica para avaliação do comprimento linear remanescente (DLL) do DCC e o volume dos tecidos mineralizados (MT) dentro do DCC nos períodos de 3, 7, 15 e 30 dias após cirurgia. Adicionalmente, foi executado análise histométrica para avaliar a composição do tecido ósseo reparado (% Osso e % Biomaterial) no período de 30 dias.Resultado O grupo COA apresentou o menor DLL e MT dentro do DCC e maior % osso do que os outros grupos. O grupo OBD apresentou maior volume de tecidos mineralizados e maior % biomaterial do que o grupo os grupos AUT e TCP. Os grupos OBD e AUT apresentaram maior % osso que o grupo TCP.Conclusão O OBD promoveu melhor padrão de aumento de disponibilidade óssea e qualidade do osso reparado em comparação ao TCP e HA/TCP, porém biologicamente inferior ao grupo AUT.
Avaliação do reparo ósseo induzido por diferentes substitutos ósseos em modelo de defeito crítico de calvária de ratos
Keywords: Histology; x-ray microtomography; bone regeneration; bone substitutes; Histologia; microtomografia; regeneração óssea; substitutos ósseos